Determinants of Labor Productivity in Indonesia: Education, Health, and Economic Infrastructure - Syabanna, Rasendriya Tsabitah; Sambodo, Herman; Binardjo, Goro; Barokatuminalloh, Barokatuminalloh (Jurnal Riset Ilmu Ekonomi, 2025)
Labor productivity in Indonesia has experienced steady growth but disparities remain and the level is still relatively low compared to neighboring ASEAN countries. This study analyzes the influence of education, health, and economic infrastructure on labor productivity using panel data from 33 provinces over the period 2010 to 2023. The analysis applies the Fixed Effect Model. The findings reveal that simultaneously, all three variables significantly impact labor productivity. However, when assessed individually, only health and economic infrastructure show a significant positive relationship while education has no statistically significant effect. These outcomes highlight the urgency of enhancing health services and expanding access to ICT, particularly in less-developed regions. At the same time, it suggest the need to refine educational policies by improving curriculum relevance to labor market demands and expanding vocational training programs to more effectively support productivity growth.